AD, Volume 7, n° 1 & 2, 1982 - Full issue - journal system (Africa Development, 1982)
CONTENTS Editorial Note Abdalla S. BUJRA ........................... I - IV La Coopération Sud-Sud : Le Plan de Lagos et l'Indépendance de l'Afrique A. BENACHENHOU ........................ 6 A Critique of the World Bank Report entitled «Accelerated DevelopmentinSub-Saharan Africa». Samir AMIN ..................... 23 Propos du Plan de Lagos sur la Science et la Technologie Fayçal YACHIR .................. 31 Central Africa Regional Co-operation in the Context of the Lagos Plan of Action Wilfred A. NDONGKO ................. 43 Commerce, Change et Regulation des économies africaines au Sud du Sahara au cours des Années 80 Joseph TEDAJO ............................ 60 L'Expérience de la Communauté de l'Afrique de l'Est dans le Context du Plan d'Action de Lagos. Ahmed MOHIDDIN ..................78 The Third United Nations Development Decade, the Monrovia Strategy and the Lagos Plan of Action : A TCDC perspective. UNDP Special Unit for TCDC .............93 L'Energie en Afrique et le Plan d'Action de Lagos Smail KHENNAS ....................102 The Changing Role of Manufacturing in African Economic Development: Trend, Prospects and Issues. Regional and Country Studies Branch, Division for Industrial Studies : UNIDO ....126 Le Plan d'Action de Lagos et les Femmes Marie Angélique SAVANE ..................142 The Lagos Plan of Action and the Development of Mineral Resources in Africa G. M. HAMID ................. 149 The Lagos Plan of Action and the World Bank on Food and Agriculture in Africa: a Comparison Thandika MKANDAWIRE ............... 166 DOCUMENTS Conférence des Directeurs d'Instituts de Recherche en Science Sociale et des Décideurs sur la Stratégie Internationale de Développement: Discours d'Ouverture du Professeur Adebayo ADEDEJI ...........178 Déclaration faite par M S.A. Ogunleye, Vice Président de la BAD à l'Occasion de la Rencontre des Gouverneurs Africains........185 Mémorandum du Groupe Africain à la Banque Mondiale et au Fonds Monétaire International ..........193 Report of the CODESRIA/ECA Conference of Directors of Social Science Research Institutes and Policy-Makers on the third United Nations Development Decade, the Monrovia Strategy and the Lagos Plan of Action ..........198 BOOKS RECEIVED ....................... 207